Perencanaan Tenaga Teknis Kefarmasian Berdasarkan Analisis Beban Kerja Menggunakan Metode WISN di RSIA KM - nurul yulaika (Universitas Airlangga, 2018)
Human Resource is one of the main factors that drive the quality of hospital services. Human Resource Planning of pharmaceutical technicians at RSIA KM posed risks to service performance. The objective of this cross-sectional study was to analyze the pharmacy staff's needs and workload by using Workload Indicators of Staffing Need (WISN) method based on real-time activity standards for each workload. RSIA KM had 4 existing pharmacy technicians. Based on the WISN analysis, the results of the study show that WISN ratio was 0.49 or ≤ 1.00 which means there was a lack of pharmaceutical staffs. The ideal number of pharmaceutical staffs should be 8.08 or 8 staffs. In response to that, RSIA KM recruited 4 pharmacy technicians. This study also discusses the implication for job enrichment and recruitment.   Keywords : human resource planning, WISN (workload indicators of staffing need), pharmaceutical technical staff